Unsteady boundary layer rotating flow and heat transfer in a copper-water nanofluid over a stretching sheet - Dzulkifli, Nor Fadhilah; Bachok @ Lati, Norfifah; M. Yacob, Nor Azizah; Md. Arifin, Norihan; Rosali, Haliza (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
This paper discussed the study of unsteady three-dimensional boundary layer rotating flow and heat transfer in Copper-water nanofluid over a stretching sheet. The partial differential equations are transformed to ordinary differential equations using the appropriate similarity variables and are then solved numerically by shooting method. The effects of unsteady parameter A, suction and injection parameters, rotating parameter Ω and volume fraction parameter φ on the skin friction coefficient, local Nusselt number together with dual velocity as well as temperature profiles are shown graphically.